Simulations of new COVID-19 pandemic waves in Ukraine and in the world by generalized SIR model - Ігор Нестерук (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï, 2022)
New waves of the COVID-19 pandemic in Ukraine, which began in the summer of 2021, and after holidays in the middle of October 2021, were characterized by the almost exponential growth of smoothed daily numbers of new cases. This is a matter of great concern and the need to immediately predict the epidemic dynamics in order to assess the maximum possible values of new cases, the risk of infection, and the number of deaths. The generalized SIR-model and corresponding parameter identification procedure were used to simulate and predict the dynamics of two new epidemic waves in Ukraine and one worldwide. Results of calculations show that new cases in Ukraine will not stop appearing before November 2022. The pandemic can continue for another ten years if the global situation with vaccination, testing, and treatment does not change.